Planning for sustainability in irrigation - Hooja, Rakesh (ed.) (New Delhi, 1994)
The book will prove useful not only for those interested specifically in the IGNP, but also for those who are interested in developmnt and management of large irrigation projects,area development, rural development planning, land waer management, regional and habitation planning, desert irrigation, farm development and agriculture extension, afforestation, drainage and irrigation engineering and the like.
Keywords: Command area development